Long-term Complications of Gluteal Augmentation Using Aquafilling Filler: A Case Report - Wünscher, Sarah Victoria; Cambiaso-Daniel, Janos; Gualdi, Alessandro; Rappl, Thomas (Indian Journal of Plastic Surgery, 2023)
The interest in gluteal augmentation using minimally invasive techniques has been increasing rapidly. Despite the fact that Aquafilling filler was described as biocompatible with human tissues, the number of associated complications has been rising.We present an exceptional case of a 35-year-old female patient, who suffered major long-term complications in association with Aquafilling filler injections in the gluteal region. The patient was referred to our center with signs of recurrent inflammation and severe pain focusing on the left lower extremity. A computed tomography (CT) scan showed multiple, communicating abscess formations all the way from the gluteal region to the lower leg. Therefore, an operative debridement was accomplished in the operating theater.Finally, this report emphasizes the severity of possible long-term complications when using Aquafilling filler especially in larger areas. Furthermore, the oncogenicity as well as toxicity of polyacrylamide, the core material of Aquafilling filler, remains uncertain, which is why further research is urgently required.
Keywords: aesthetic surgery; buttock; polyacrylamide